Analisis Manajemen Risiko Rantai Pasok Pada Produk Alat Berat Penunjang Industri Pertambangan - Sawarni Hasibuan; Muhamad Atho R (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
Manufacturing activities such as trailer products potentially generate various risks. This research aims to analyze risk management in the supply chain of trailer production using the House of Risk (HOR) model. The business activities mapping is using the Supply Chain Operations Reference (SCOR) method which consists of 6 parts of the management process, plan, source, make, deliver return and enable. Research is conducted through two phases of HOR. The HOR 1 activities are the identification of risk events and risk agents based on SCOR mapping, measurement of severity, and occurrence levels to produce an Aggregate Risk Priority (ARP), then determine a priority risk agent in the mitigation process. The HOR 2 is used to determine which actions are to be done ﬁrst, considering their differing effectiveness as well as resources involved and the degree of difﬁculties in performing. The company should ideally select a set of actions that are not so difﬁcult to perform but could effectively reduce the probability of risk agents occurring. 7 experience respondents were involved in the study consisting of engineering, procurement, production, warehouse, production planning, after-sales dan quality control. The results of the analysis successfully identified 46 risk events and 41 risk agents in the manufacturing of mining trailers. FGD and Pareto analysis used in the study produced 16 recommendations for mitigation actions that are expected to be able to mitigate risk.